A study of the Cymbals by Mike Portnoy’s dance of eternity / Mohd Hasanul Abu Bakar - Abu Bakar, Mohd Hasanul (2019)
Drum is a complex music instrument consisting a few external parts which are tom-tom, floor tom, snare, bass drum and cymbals. The core of this research is to explore the playing of cymbals on pieces Dance of Eternity by Mike Portnoy. In this analysis, the writer is focuses on Mike Portnoy in the piece that have element of progressive rock. It is rare to find any analysis on the playing cymbals on this piece by Mike Portnoy. Most sources of information nowadays only stresses on the techniques of playing, skills and rudiments of playing, and types of cymbal and drum sets commonly used. However, none has stated on the playing cymbals on this piece. The writer purposely choose Mike Portnoy as a drummer for analysis that have one thing in common, which is they are using cymbal endorsed by the Sabian Company. The Sabian has custom-made their cymbals to suit this drummer's technique of playing and music styles that he plays.